Comparing translational population‐PBPK modelling of brain microdialysis with bottom‐up prediction of brain‐to‐plasma distribution in rat and human. (17th September 2014) - Ball, Kathryn; Bouzom, François; Scherrmann, Jean‐Michel; Walther, Bernard; Declèves, Xavier; Tamai, Ikumi
ABSTRACT The prediction of brain extracellular fluid (ECF) concentrations in human is a potentially valuable asset during drug development as it can provide the pharmacokinetic input for pharmacokinetic–pharmacodynamic models. This study aimed to compare two translational modelling approaches that can be applied at the preclinical stage of development in order to simulate human brain ECF concentrations. A population‐PBPK model of the central nervous system was developed based on brain microdialysis data, and the model parameters were translated to their corresponding human values to simulate ECF and brain tissue concentration profiles. In parallel, the PBPK modelling software Simcyp was used to simulate human brain tissue concentrations, via the bottom‐up prediction of brain tissue distribution using two different sets of mechanistic tissue composition‐based equations. The population‐PBPK and bottom‐up approaches gave similar predictions of total brain concentrations in both rat and human, while only the population‐PBPK model was capable of accurately simulating the rat ECF concentrations. The choice of PBPK model must therefore depend on the purpose of the modelling exercise, the in vitro and in vivo data available and knowledge of the mechanisms governing the membrane permeability and distribution of the drug. Copyright © 2014 John Wiley & Sons, Ltd.